2022
DOI: 10.1155/2022/4877422
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Hybrid Power System Model Based on Solar and Wind Energy for Integrated Grids

Abstract: Global energy needs have risen in recent years, and traditional energy sources such as fossil fuels are no longer viable. To meet the growing electricity demand, attention has moved to renewable energy sources such as solar and wind energy. Furthermore, the development of clean energy is vital for combating climate change. Various studies have shown the effectiveness of using hybrid systems (combination of solar photovoltaic and wind energy systems) for generating power. However, a significant amount of energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The study suggested that the optimized PV/battery/thermal storage system could not meet the entire energy demand, needing additional sources of heat and power. Jha et al [29] proposed a dual-energy generating system integrated with a grid to reduce energy waste. The load data was compiled from several areas of Rajasthan, India.…”
Section: Figure 1 Average Solar Radiationmentioning
confidence: 99%
“…The study suggested that the optimized PV/battery/thermal storage system could not meet the entire energy demand, needing additional sources of heat and power. Jha et al [29] proposed a dual-energy generating system integrated with a grid to reduce energy waste. The load data was compiled from several areas of Rajasthan, India.…”
Section: Figure 1 Average Solar Radiationmentioning
confidence: 99%
“…(1) Use of a diesel generator for enhancing system reliability, however not a suitable option given environmental constraints (2) A signifcant impact of only RESs-based system on CO 2 emissions and overall system cost (3) An abundance of RESs leads to reduced COE and overall gas emissions PV-wind-batterygrid [27] Rajasthan, India Te input of estimated load data, considering the number of households and essential electrical appliances, is given to HOMER Pro software [35,36]. Te scaled value of the annual average load per day (kWh/d) is considered.…”
Section: System Design Location Assessment Aspects Remarksmentioning
confidence: 99%
“…Also, the study mentioned that the CC method minimized the financial indicators of the optimal solution more than other strategies. Some other relevant studies of the technoeconomic feasibility of HES have focused on three major groups, comparison procedures [27], design and planning [28][29][30], and energy management [31,32]. The project lifetime in all of these research articles has been set at 20 or 25 years, with no consideration of the impacts of reducing the project's lifetime.…”
Section: Introductionmentioning
confidence: 99%